Hashtagging Your Health: Using Psychosocial Variables and Social Media Use to Understand Impression Management and Exercise Behaviors in Women - (:unkn) unknown (My University, 2016)
Our society has become heavily reliant on social media, especially in the health and exercise domain. Social and environmental factors impact females’ body image perceptions and create body image disturbances, yet little research is dedicated to the exploration of how social media, and social comparisons through social media exposure, impact exercise behaviors and body image perceptions in females. Considering Perloff's (2014) theoretical model, the current study explored how the interaction between individual psychosocial variables and social media use predict exercise behaviors and engagement in impression management in women. Using a mixed methodological approach, the specific aims of this study were to explore (1) how psychosocial behaviors and social media use predict exercise behaviors and engagement in impression management; (2) the relationship between exercise behaviors, frequency of social media use, and content posted to social media; (3) how social media influences women’s thoughts, perceptions, and conceptualizations of a healthy body and healthy exercise behaviors. Two studies were conducted using both quantitative and qualitative methods to explore associations in recreationally active women. The results of these studies provide insight into the complexities of social media and its influence on exercise behaviors and impression management, providing information that may be used to develop future interventions to increase body positivity on social media and improve exercise experiences.
Keywords: Exercise; Health Behaviors; Impression Management; Psychsocial Behaviors; Social Media